Implementation of Mineral and Coal Mining Licensing In Indonesia After Presidential Regulation of 2022 - Aulia, Kevin; Ginting, Budiman; Siregar, Mahmul; Sukarja, Detania (Locus: Jurnal Konsep Ilmu Hukum, 2024)
This study examines the management of mining licenses, focusing on the impact and effectiveness of mineral and coal mining permits after Presidential Regulation No. 55/2022. Using a juridical normative approach with literature and field studies, it finds that Law No. 3/2020 shifted key licensing authority for non-metal mineral and rock mining from the Governor to the Central Government. The regulation then delegated permit issuance and oversight to the Provincial Government, changing regional authority from attributive to delegated. In practice, both the law and the regulation have not effectively resolved mining-related issues.